1999
DOI: 10.1056/nejm199902113400603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroxine as Compared with Thyroxine plus Triiodothyronine in Patients with Hypothyroidism

Abstract: In patients with hypothyroidism, partial substitution of triiodothyronine for thyroxine may improve mood and neuropsychological function; this finding suggests a specific effect of the triiodothyronine normally secreted by the thyroid gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
282
3
17

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(309 citation statements)
references
References 13 publications
7
282
3
17
Order By: Relevance
“…Our patient initially received 200 µg of T4 intravenously, followed by a combination of T3 and T4 given orally. The combination of T4 and T3 has been reported to benefit some patients with myxedema madness (29). As in most reported cases, our patient was also treated with antipsychotic drugs.…”
Section: Discussionsupporting
confidence: 60%
“…Our patient initially received 200 µg of T4 intravenously, followed by a combination of T3 and T4 given orally. The combination of T4 and T3 has been reported to benefit some patients with myxedema madness (29). As in most reported cases, our patient was also treated with antipsychotic drugs.…”
Section: Discussionsupporting
confidence: 60%
“…This may be explained by the lack of direct thyroidal T 3 production, which accounts for approximately 20% of circulating T 3 , and/or a reduced 5 0 deiodinase activity in patients with a defective thyreotrope axis. It remains to be determined whether adding small doses of T 3 would be beneficial in CH patients, as has been proposed in primary hypothyroidism (22). Alternatively, targeting higher fT 4 levels would likely lead to normalisation of fT 3 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of apparently optimal T 4 substitution therapy (securing normal serum TSH levels), reduced quality of life (QOL) has been described in these patients as compared to the healthy subjects (7). In 1999, Bunevicius described an increase in wellbeing in substituted hypothyroid subjects when comparing combination therapy with T 4 and T 3 to monotherapy with T 4 (8). Later, ten studies have been performed including a total of w1000 patients, and based on these studies a recent meta-analysis concluded that there seems to be no evidence supporting superior effect of combination treatment (9).…”
Section: Introductionmentioning
confidence: 99%